2007
DOI: 10.1088/0954-3899/34/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Transport model analysis of the transverse momentum and rapidity dependence of pion interferometry at SPS energies

Abstract: Based on the UrQMD transport model, the transverse momentum and the rapidity dependence of the Hanbury-Brown-Twiss (HBT) radii R L , R O , R S as well as the cross term R OL at SPS energies are investigated and compared with the experimental NA49 and CERES data. The rapidity dependence of the R L , R O , R S is weak while the R OL is significantly increased at large rapidities and small transverse momenta. The HBT "life-time" issue (the phenomenon that the calculated R 2 O − R 2 S value is larger than the corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 57 publications
(88 reference statements)
3
20
0
Order By: Relevance
“…This may be, at least partially, why the predictions from UrQMD more closely match the energy dependence of the data compared to the hydrodynamic predictions. While it does not explicitly contain a deconfined state, it does incorporate color For the azimuthally integrated results, UrQMD does rather well at predicting the observed dependence of HBT radii on k T and centrality [79,80]. As discussed earlier, inclusion of a mean field acting between pre-formed hadrons (color string fragments) predicts R out /R side ratios similar to the observed values and leads naturally to a minimum in the volume similar to that which is observed experimentally [72,73].…”
Section: Kinetic Freeze-out Eccentricitymentioning
confidence: 99%
“…This may be, at least partially, why the predictions from UrQMD more closely match the energy dependence of the data compared to the hydrodynamic predictions. While it does not explicitly contain a deconfined state, it does incorporate color For the azimuthally integrated results, UrQMD does rather well at predicting the observed dependence of HBT radii on k T and centrality [79,80]. As discussed earlier, inclusion of a mean field acting between pre-formed hadrons (color string fragments) predicts R out /R side ratios similar to the observed values and leads naturally to a minimum in the volume similar to that which is observed experimentally [72,73].…”
Section: Kinetic Freeze-out Eccentricitymentioning
confidence: 99%
“…Only the negatively charged pions are considered during the analyzing process (for each analysis, one hundred million pion pairs are considered). For the cascade calculations, we take the results from our previous publications as reference [13,23]. We found that the residual Coulomb effect after the hadron freeze-out on the HBT radii of the pion source is small [25], therefore we omit it in the present analysis.…”
Section: Crab Analyzing Program and The Fitting Processmentioning
confidence: 99%
“…We concentrate here on the two (identical) pion interferometry and test the sensitivity of the HBT results on different stages of the evolution. In our previous investigations on the HBT correlation of various identical particle pairs from HICs at AGS, SPS, and RHIC energies [13,22,23,24,25,26], we adopted the UrQMD model but further considered the mean field potentials for both confined and "pre-formed" particles in the model [13,25,26]. We found that also initial stage interaction may contribute to a better description of the HBT time-related puzzle throughout the energies from AGS, SPS, up to RHIC.…”
Section: Introductionmentioning
confidence: 99%
“…5 (c)): The calculated values of R 2 O − R 2 S are about 3.5 ∼ 5 fm while the measured ones are 1.5 ∼ 4 fm. Many efforts have been put forward over the last years to clarify this issue [39,44,38,46,45,28,27,25]. Here, we show in Fig.…”
Section: Pos(cpod07)048mentioning
confidence: 74%